Strategic development plan for rural tourism based on a cluster model (example of Cherkasy region) - Довгань, Наталія Степанівна; Reimann, Mart; Тарабарова, Інна (Київський національний університет імені Тараса Шевченка, 2025)
Background. Modern rural development in Ukraine necessitates innovative solutions, as communities face demographic decline and economic pressures. The implementation of tourism clusters has emerged as a promising mechanism for enhancing local resilience and strengthening cooperation among key stakeholders. Collaborative Ukrainian-Estonian initiatives carried out from 2021 to 2024 provide evidence of the positive impact of shared expertise, hackathons, and networking on shaping community-based tourism strategies. These projects underscore the increasing significance of tourism in diversifying rural economies and fostering a professional environment for sustainable regional development. Methods. The research methodology combined social and economic-organisational approaches, which allowed for a comprehensive assessment of communication processes and the potential for partnership interaction within rural communities. Primary data were collected through surveys (over 250 interviews) and a hackathon, which provided an opportunity to test hypotheses, evaluate the level of cooperation between stakeholders, and identify opportunities for forming tourism clusters. Results. This article discusses the modern transformations of rural territories within the context of the transition from a productive to a post-productive development model, as well as the role of tourism in these processes. It highlights the key characteristics of rural areas and examines the range of tourism and recreational activities that contribute to the attractiveness of rural spaces. It is shown that the development of rural tourism contributes to economic diversification, the preservation of cultural heritage, the strengthening of social cohesion, and an improvement in quality of life. At the same time, the sector's limitations are outlined, including its fragmentation, lack of competencies, and limited financial resources. Based on the results of stakeholder surveys and a practical hackathon in the Cherkasy region, key challenges and strategic opportunities for the development of rural tourism are identified. The effectiveness of a cluster approach for uniting businesses, communities, authorities, and educational institutions to create a competitive tourism product is demonstrated. The importance of international experience, particularly Estonian, for enhancing institutional capacity and the sustainability of regional tourism clusters is emphasised. The article offers strategic guidelines for the development of rural tourism as a tool for sustainable territorial development in Ukraine. Conclusions. The transformation of rural tourism is only possible through stable cooperation among all participants, based on mutual trust and respect. The cluster approach serves as a key mechanism for development, capable of ensuring economic diversification, preserving cultural heritage, strengthening social cohesion, and creating a competitive and sustainable tourist region.

Вступ. Сучасний розвиток сільських територій в Україні вимагає інноваційних рішень, оскільки громади стикаються з демографічним спадом та економічним тиском. Впровадження туристичних кластерів стало перспективним механізмом підвищення локальної стійкості та зміцнення співпраці між ключовими зацікавленими сторонами. Спільні українсько-естонські ініціативи, реалізовані з 2021 по 2024 рік, свідчать про позитивний вплив обміну досвідом, хакатонів та мережевих заходів на формування стратегій розвитку туризму на основі громади. Ці проєкти підкреслюють зростаюче значення туризму у диверсифікації сільських економік та створенні професійного середовища для сталого регіонального розвитку. Методи. Методологія дослідження поєднувала соціальні та економіко-організаційні підходи, що дало змогу всебічно оцінити процеси комунікації та потенціал партнерської взаємодії в сільських громадах. Основні дані було зібрано шляхом опитувань (понад 250 інтерв’ю), а також під час хакатону, що дав змогу перевірити гіпотези, оцінити рівень співпраці між зацікавленими сторонами та визначити можливості для формування туристичних кластерів. Результати. У статті обговорено сучасні трансформації сільських територій у контексті переходу від продуктивної до постпродуктивної моделі розвитку, а також роль туризму в цих процесах. Висвітлено ключові характеристики сільських районів та проаналізовано спектр туристичних і рекреаційних заходів, що сприяють привабливості сільських просторів. Показано, що розвиток сільського туризму сприяє економічній диверсифікації, збереженню культурної спадщини, зміцненню соціальної згуртованості та поліпшенню якості життя. Водночас окреслено обмеження сектору, зокрема його фрагментацію, брак компетенцій та обмежені фінансові ресурси. За результатами опитувань зацікавлених сторін та практичного хакатону в Черкаській області визначено ключові виклики та стратегічні можливості розвитку сільського туризму. Продемонстровано ефективність кластерного підходу для об’єднання бізнесів, громад, органів влади та освітніх закладів для створення конкурентного туристичного продукту. Підкреслено важливість міжнародного досвіду, зокрема естонського, для підвищення інституційної спроможності та сталості регіональних туристичних кластерів. Запропоновано стратегічні орієнтири для розвитку сільського туризму як інструменту сталого територіального розвитку в Україні. Висновки. Трансформація сільського туризму можлива лише за умови стабільної співпраці всіх учасників, основаної на взаємній довірі. Кластерний підхід виступає як ключовий механізм розвитку, здатний забезпечити економічну диверсифікацію, збереження культурної спадщини, зміцнення соціальної згуртованості та створення конкурентного і сталого туристичного регіону.
Стратегічний план розвитку сільського туризму на основі кластерної моделі (приклад Черкаської області)
Andersson, T., Schwaag Serger, S., Sörvik, J., & Wise Hansson, E. (2004). The Cluster Policies Whitebook. IKED – International Organisation for Knowledge Economy and Enterprise Development, Malmö, Sweden. Association Agreement between the European Union and its Member States, of the one part, and Ukraine, of the other part. (2014, May 29). OJ L 161. https://www.bilaterals.org/IMG/pdf/eu-ukraine-association-agreement-english.pdf Brigita Gajšek, & Jure Kovač (2016). Key factors for the successful operation of clusters: the case for Slovenia. Organizacija. Volume 49, issue 2 (MAY 2016). Рр. 151–160. https://doi.org/10.1515/orga-2016-0011 Burns, P., & Holden, A. (1995). Tourism, a New Perspective. Prentice Hall. Butler, R., & Hall, C.M. (1998). Conclusion: The sustainability of tourism and recreation in rural areas. In R. Butler, C. M. Hall, and J. M. Jenkins, (Еds). Tourism and Recreation in Rural Areas. John Wiley & Sons, Chichester, pp. 249–258. Cherep A. V., & Venherska N. S. (2022). Diversification of European rural tourism through innovation and creativity: educational and practical guide. Helvetika publishing house [in Ukrainian]. [Череп, А.В., & Венгерська, Н.С. (2022). Диверсифікація європейського сільського туризму через збалансованість та креативність. Видавничий дім "Гельветика"]. Development Strategy of Cherkasy Region for the Period 2021-2027 [in Ukrainian]. [Стратегія розвитку Черкаської області на період 2021–2027 роки]. https://strategy2027-ck.gov.ua/wp-content/uploads/2021/01/Strategiya-rozvytku-CHerkaskoyi-oblasti-2021-2027.pdf Dovhan, N., & Tarabarova, I. (2024). Rural tourism in Cherkasy region: communication, partnership, and cluster cooperation. Economic and Social Geography, 91, 64–72 [in Ukrainian]. [Довгань, Н., & Тарабарова, І. (2024). Сільський туризм Черкащини: комунікація, партнерство та кластерна співпраця. Економічна та соціальна географія, 91, 64–72]. https://doi.org/10.17721/2413-7154/2024.91.64-72 Eesti Maaturismi Ühing – Estonian Rural Tourism Organization. RuralTour – European Federation of Rural Tourism. https://www.ruraltour.eu/organizations/estonianruraltourism#:~:text=travel%20associations%2C%20schools%20teaching%20tourism,shared%20its%20experience%20in%20many European Commission. (2008). The concept of clusters and cluster policies and their role for competitiveness and innovation – Main statistical results and lessons learned. Brussels: Commission Staff Working Document, SEC (2008) 2637 Information on the implementation status of the Cherkasy Region Tourism Development Programme for 2021–2025, in 2021 and 2022 [in Ukrainian]. [Інформація про стан виконання заходів Програми розвитку туризму Черкаської області на 2021–2025 роки, у 2021 році та 2022 році]. https://www.oblradack.gov.ua/files/docs/Zvit_prog/Zvit_5_18_8_19022021_2022.pdf INNO Germany AG. (2010). Clusters and clustering policy: a guide for regional and local policy makers. European Union. Ketels, C.H.M. (2011). Clusters and Competitiveness: Porter’s Contribution. Chap. 10. In R. Huggins, H. Izushi (Eds), Competition, Competitive Advantage, and Clusters: The Ideas of Michael Porter (pp. 173–192). Oxford University Press. https://doi.org/ 10.1093/acprof:oso/9780199578030.003.0010 Leite, H. de L. K., Binotto, E., Padilha, A. C. M., & Hoeckel, P. H. de O. (2023). Cooperation in rural tourism routes: Evidence and insights. Journal of Hospitality and Tourism Management, 57, 84–96. https://doi.org/10.1016/j.jhtm.2023.09.005 Lorleberg, W., Hensche, H.-U., Schleyer, A., & Wildraut, C. (2010). Standortsicherung durch Clustermanagement und Netzwerkentwicklung – eine Perspektive für die Agrarwirtschaft in NRW. Soest: Fachhochschule Südwestfalen, Hochschule für Technik und Wirtschaft. Malska, M. P., & Zinko, Yu. V. (2018). Types and models of rural tourism clusters in Ukraine. Bulletin of the Kyiv National University of Culture and Arts, 2, 8–23 [in Ukrainian]. [Мальська М., & Зінько Ю. (2018). Типи і моделі кластерів сільського туризму в Україні. Вісник Київського національного університету культури і мистецтв. Серія: Туризм, 2, 8–23]. https://doi.org/10.31866/2616-7603.2.2018.154397 MTÜ Eesti Maaturism. https://www.maaturism.ee/index.php?id=mtu-eesti-maaturism NGO "Tourist movement of Chigyrin region". [in Ukrainian]. [ГО "Туристичний рух Чигиринщини"]. https://www.facebook.com/groups/834479533289941/ PO "Union of Rural Green Tourism of Ukraine". https://greentour.com.ua/en/ukrainian-guest-houses/ Porter, M. E. (1998). Cluster and the new economics of competion. Harward Business Rewiew, 6(76), 77–90. Porter, M. E., & Ketels, C.H.M. (2009). Clusters and Industrial Districts – Common Roots, Different Perspectives. In G. Becattini, M. Bellandi, & L. De Propris (Eds.), The Handbook of Industrial Districts. Edward Elgar Publishing. Reimann, M., Zinko, Yu., Zapototskyi, S., Dovhan, N., Okolovych, I., & Printsmann, A. (2023). Clustering of rural tourism in Ukraine. PE Yamchynskyi O. V. Roberts, L., & Hall, D. (2001). Rural tourism and recreation: principles to practice (pp. 24–52; 219–227). CABI Publishing. Ministry of Agrarian Policy and Food of Ukraine. (2024, April 12). Rural development [in Ukrainian]. [Міністерство аграрної політики та продовольства України. (2024, 12 квітня). Сільський розвиток]. https://minagro.gov.ua/napryamki/rozvitok-silskih-teritorij Sgouro Melisidou, A., Papageorgiou, A., Papayiannis, D., & Varvaressos, S. (Decemder, 2014). Tourism clusters as a potentially effective tool for local development and sustainability. Review of Tourism Sciences, 9, 218–232. https://jotr.eu/index.php/volume9/75-melissidou To plan and implement Cluster strategies. Global Protection Cluster. https://globalprotectioncluster.org/node/1043
Keywords: сільський туризм; кластерний підхід; туристичні кластери; розвиток сільських територій; економічна диверсифікація; Черкаська область; rural tourism; cluster approach; tourist clusters; development of rural areas; economic diversification; Cherkasy region